The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12887-022-03682-8
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between Helicobacter pylori infection and childhood asthma in a physical examination population: a cross-sectional study in Chongqing, China

Abstract: Background Childhood asthma has substantial effects on children's health. It is important to identify factors in early life that influence childhood asthma. Accumulating evidence indicates that Helicobacter pylori may protect against allergic diseases. This study aimed to evaluate the relationship between H. pylori infection and pediatric asthma in Chongqing, China. Materials and methods This cross-sectional study included healthy children aged 4–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The relative abundance of Proteobacteria phylum and Firmicutes: Bacteroidetes ratio was related to the stability of microbial community, pro‐inflammatory response, and energy metabolism, which played an important role on maintaining gut microbial homeostasis, 50 the expansion of Proteobacteria was concluded to be a potential marker for unstable microbial community and some metabolic and immune disease in a review, 51 increased value of Firmicutes/Bacteroidetes was found in animal models of NAFLD, 52 but their role on maintaining stomach microbial homeostasis remained unknown. In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori ‐infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma 53‐55 . Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The relative abundance of Proteobacteria phylum and Firmicutes: Bacteroidetes ratio was related to the stability of microbial community, pro‐inflammatory response, and energy metabolism, which played an important role on maintaining gut microbial homeostasis, 50 the expansion of Proteobacteria was concluded to be a potential marker for unstable microbial community and some metabolic and immune disease in a review, 51 increased value of Firmicutes/Bacteroidetes was found in animal models of NAFLD, 52 but their role on maintaining stomach microbial homeostasis remained unknown. In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori ‐infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma 53‐55 . Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, the abundance of Proteobacteria and Firmicutes: Bacteroidetes ratio declined significantly in H. pylori-infected patients, which may illustrate the protective effect of H. pylori on inflammatory bowel disease and child asthma. [53][54][55] Firmicutes:Bacteroidetes ratio might be a potential marker for inflammation of gastric mucous, increased value of Firmicutes/Bacteroidetes may represent a higher risk of oncogenesis. The infection of H. pylori may be a result of individual gastric flora disturbance, such as the imbalance of Firmicutes and Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study that included 2241 participants, the rates of asthma diagnosis were 7.23% among H. pylori -negative children and 3.77% among H. pylori -positive children. This result indicates a significant inverse correlation between H. pylori infection and asthma ( Wang et al., 2022a ). This protective effect by H. pylori is supported by three hypotheses, including the gut-lung axis theory, the “disappearing microbiota” hypothesis, and the hygiene hypothesis ( Strachan, 2000 ; Taube and Müller, 2012 ; Wypych et al., 2019 ).…”
Section: Clinical Diseasesmentioning
confidence: 94%
“…Epidemiological studies have shown a decline in the prevalence of H. pylori infection in the Western World and in some developing countries in contrast to an increase in the incidence of asthma and allergic diseases [ 8 ]. Studies have demonstrated that H. pylori infection can prevent asthma [ 9 , 10 ], and it has been noted that CagA-positive H. pylori infection is significantly negatively associated with the risk of asthma [ 11 , 12 ] and may even be negatively associated with the severity of asthma [ 11 ]. A meta-analysis of 18 cross-sectional studies found that H. pylori infection, especially CagA-positive H. pylori infection, was inversely associated with the prevalence of asthma [ 13 ].…”
Section: Association Between H Pylori Infection and The Risk Of Aller...mentioning
confidence: 99%